Distribution and abundance of microplastics in urban and industrial wastewater treatment plants in Tabriz metropolis - Mohammad Javad Nematollahi; Mahsa Mobasheri; Zeinab Esmaeili; Mohammadreza Mahmoudi; Niloofar Yousefi; Rosa Busquets (Scientific Reports)
Abstract Wastewater treatment plants (WWTPs) are routes through which microplastics (MPs) enter the environment. This research assesses MP occurrence in 2 urban and 5 industrial WWTPs, in a city of 1.6 M inhabitants (Tabriz, Iran). The sampling schedule helps quantify the city’s MP release into surface water. One of the urban WWTPs in the study used tertiary treatment, whereas the rest of the plants only had primary and secondary treatments. MPs were not efficiently removed in the urban WWTPs: 255 ± 55 MP/L (influent) and 240 ± 50 MPs/L (effluent). In the industrial WWTPs, there was some elimination of MPs: 246 ± 169 MP/L (influent) and 94 ± 72 MPs/L (effluent). The lowest MP removal, < 10%, corresponds to urban treatment. The influents had > 1–5 mm MP particles at 14% of the total MPs in the incoming sewage, and such fraction was just < 2% of the total MPs in the effluents. In contrast, smaller MPs, especially those < 250 μm (the smallest detectable and confirmed MP was 50 μm), were the most abundant MP fraction in the treated effluents. Fibres, black MPs and particles ranging from 100 μm to < 250 μm prevailed in influents and effluents of both urban and industrial WWTPs. In the wastewater of both types of plants, the MPs were mainly composed of polyamide and polycarbonate. This research confirms that urban and industrial wastewater are important MP contributors to receiving water and calls for improvements in wastewater treatments to decrease the uncontrolled entry of MPs into the environment.